Rubiano Muñoz, R. (2011). Prensa y tradición. La imagen de España en la obra de Miguel Antonio Caro. Bogotá: Siglo del hombre / UDEA. ISBN: 9586651738. Número de páginas: 232. - López Jiménez, Carlos Arturo; Pontificia Universidad Javeriana (2011)
null